Function and Meaning of Metaphors in The Palm-Leaf Manuscript of Cilinaya Written in Sasak Language and its Translation - Sarwadi; Ida Bagus Putra Yadnya; N.L. Sutjiati Beratha,; Ida Ayu Made Puspani (The Doctoral Studies Program of Linguistics of Udayana University, 2019)
The palm-leaf manuscript of Cilinaya is one of the manuscripts which is stillimplemented in the life of the Sasak ethnic people. The writer conveyed massages to the readersusing different figurative expressions, one of which is metaphor. This current study is a product-oriented translation study in which the qualitative descriptive approach was applied. The palm-leaf manuscript of Cilinaya was used as the data source. Based on the result of analysis anddiscussion, it can be concluded that several metaphorical expressions are used to praise abeautiful girl that everybody is proud of. Those metaphorical expressions are Duh mas mirahkembang mete, Duh mas mirah serining kasur, Duh mas mirah buaq bulu, Neneq bini, Dun dendare masku, Dendare, dende, Duh mas mirah dende ayu. In the Sasak language, a metaphor willhave different function and meaning if the morpheme „be‟ is inserted in the expression „lauhdaye’ to form „belauk bedaye‟.